Pengaruh Seduhan Kayu Manis Terhadap Kadar Gula Darah Pada Penderita DM tipe II - Azmaina, Azmaina; Juwita, Lisavina; Amelia, Sherly (Universitas Fort De Kock Bukittinggi, 2021)
Background: Diabetes Mellitus Type II is the most common form of diabetes. It causes vary from predominantly insulin resistance to insulin resistance defects. According to the data from the Community Health Office of Sungai Penuh City from 2016 to 2018, Diabetes Mellitus is the most cases found in Kumun Community Health Center. They were 299 cases insulin receptor protein on cells. This study aims to determine The Influence of Cinnamon Steeping toward Blood Sugar Levels in Patients with Type II DM in Kumun Kota Sungai Penuh Community Health Center Working Area in 2020. Methods: It was a Quasi Experiment with one group pretest posttest design approach. This research was carried out on November to December 2020. The population was all diabetes mellitus sufferers type II in Kumun Community Health Center Working Areaby using purposive sampling technique, 20 people were chosen as the samples. The data were processed by computerization with univariate and bivariate analysis by using the Paired Sample T Test. Results: The results showed that the average blood sugar level after being given steeping cinnamon was 148.95 mg/dL. Based on the statistical test, it was found that p = 0.000. Conclusion: It can be concluded that there is an effect of cinnamon infusion on reducing blood sugar levels in diabetes mellitus patients type II. It is hoped that all parties use cinnamon to help reduce blood sugar levels in patients with diabetes mellitus type II.Keywords: Cinnamon, Diabetes Mellitus, Blood Sugar Levels